Diagnostic value of procalcitonin for acute complicated appendicitis - Yamashita, Hiromasa (Nagoya J Med Sci, 2016)
A rapid and reliable test for detection of complicated appendicitis would be useful when deciding whether emergency surgery is required. We investigated the clinical usefulness of procalcitonin for identifying acute complicated appendicitis. We retrospectively analyzed 63 patients aged ≥15 years who underwent appendectomy without receiving antibiotics before admission and had preoperative data on the plasma procalcitonin level (PCT), body temperature (BT), white blood cell count (WBC), neutrophil / lymphocyte ratio (N/L ratio), and C-reactive protein level (CRP). Patients were classified into 3 groups: group A (inflammatory cell infiltration of the appendix with intact mural architecture), group B (inflammatory cell infiltration with destruction of mural architecture, but without abscess or perforation), and group C (macroscopic abscess and/or perforation). For identifying destruction of mural architecture, the diagnostic accuracy of PCT was similar to that of BT or CRP. However, the diagnostic accuracy of PCT was highest among the five inflammatory indices for identifying abscess and/or perforation, with the positive predictive value of PCT for abscess and/or perforation being higher than that of CRP (73% vs. 48%). Univariate analysis of the predictors of abscess and/or perforation revealed that a plasma PCT level ≥0.46 ng/mL had the highest odds ratio (30.3 [95% confidence interval: 6.5–140.5] versus PCT <0.46 ng/mL). These findings indicate that procalcitonin is a useful marker of acute appendicitis with abscess and/or perforation.